Karakteristik Organoleptik Susu dengan Penambahan Sari Kurma (Phoenix dactilyfera L.) pada Level Berbeda - Sabil, Syahriana; Amin, Muhammad; Mirnawati; Risal, Muhammad; Rusman, Rusni Fitri Y (Jurnal Ilmu dan Industri Peternakan, 2023)
The purpose of this study was to determine the concentration of different date palm juice that could affect the organoleptic characteristics including color, taste, aroma, and preference of date milk. The research method was carried out experimentally using completely randomized design (CRD). The treatment factorial was the level of addition of date palm juice (0, 10, 15 and 20%). Each treatment was repeated 3 times. The results showed that the addition of date palm juice had a significant effect (P<0.01) on the panelist's assessment of color, taste and preference. The results of the analysis of variance showed that there was a very significant difference (P>0.05) in the assessment of color, taste, aroma and preference between milk without the addition of date juice and milk with the addition of date juice. The higher the level of addition of date juice to milk, the color of the product is getting a little brown, the taste is sweeter, the aroma of milk is reduced, the aroma of dates is more pronounced and the consumers prefer it. The addition of date juice to milk affects the organoleptic characteristics of color, taste, aroma, and preference for date milk. the level of date juice administration (20%) gave the product characteristics favored by the panelists.